Chylothorax and chylous as - Weiss, M.; Schwarz, F.; Wallmichrath, J.; Baumeister, R.; Frick, A.; Bartenstein, P.; Rominger, A. (Nuklearmedizin - NuclearMedicine, 2015)
The aim was to analyze conventional planar scintigraphy and SPECT/CT in patients clinically suspicious for chylothorax or chylous ascites. Lymphoscintigraphy was performed for two reasons: first, to help diagnose chylothorax or -abdomen, by demonstrating diffuse uptake in fluid accumulations, and then secondly, to detect the site of leakage to test the prediction that additional use of SPECT/ CT-technique improves upon the diagnostic value of planar lympho scintigraphy in the baseline detection of thoraco-abdominal lymphatic disorders. Patients, material, methods: From 7/2008-7/2014 a total of 24 consecutive patients (8 woman, 16 men; age, range 31-79 years) presenting with clinical symptoms suspicious for chylothorax and/or chylous ascites were examined by planar lymphoscintigraphy (n = 26) and additional tomographic SPECT/CT- (n = 22) or SPECTtechnique (n = 2). Results: Chylothorax could be scintigraphically confirmed in n = 9, chylous ascites in n = 5 scintigraphies, and excluded in n = 10 patients. In all planar scintigraphy findings of pathological lymph drainage regions (n = 14), SPECT/CT delivered additional relevant information, notably the anatomic localization of the lymphatic leakage. For the baseline detection of thoraco-abdominal lymphatic transport disorders, lymphoscintigraphy showed sensitivity of 88%, specificity of 100%, positive predictive value of 100%, and negative predictive value of 80%. Conclusions: Our findings show that due to the particular advantages presented by tomographic separation of overlapping sources, SPECT/CT specifies better the anatomical sites, improving the localization of lymphatic leakage in aid of planning surgical re-interventions.
Keywords: Chylothorax; chylous ascites; lymphoscintigraphy; SPECT/CT; hybrid imaging